Lessons from the street: Using street art to disrupt misrepresentations and invisibility of Indigenous women and girls in Canadian mass media - Rodrigues, Anna Augusto (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2025)
This article discusses the potential of street art to counter misrepresentations of Indigenous women and girls in Canadian mass media, where common tropes of being incompetent mothers or criminals, amongst others, are pervasive. In this article, I look at examples of street art that showcase Indigenous women as caring, empowered, and knowledgeable individuals. These examples of street art generate not only alternative narratives on Indigenous mothering, agency, and knowledge but also provide visibility, as research shows the stories of Indigenous women and girls are not consistently seen in Canadian mass media. Negative representations of Indigenous women and girls have been connected to the violence they experience in Canada; therefore, disrupting these misrepresentations and stereotypes is of vital importance.